2018
DOI: 10.1016/j.electacta.2018.06.179
|View full text |Cite
|
Sign up to set email alerts
|

Fused and unzipped carbon nanotubes, electrochemically treated, for selective determination of dopamine and serotonin

Abstract: Glassy carbon electrodes (GC) were modified with multiwalled carbon nanotubes (MWCNT/GC) and electrochemically treated first by applying an oxidation potential and then a reduction potential. The resulting electrodes were characterized via scanning electron microscopy, Raman spectroscopy, energy dispersive spectroscopy, and electrochemical techniques, particularly cyclic voltammetry using the redox probes Fe(CN) 6 3-/4and Ru(NH 3) 2+/3+ and electrochemical impedance spectroscopy using Fe(CN) 6 3-/4-. These mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Electrochemical characterisation of these electrodes is shown in Figure 2 for outer sphere redox species hexaamineruthenium (III) chloride. [21] In the vertical orientation print, clear voltammetric peaks were observed (Figure 2A, n=4), with significant reduction in the cathodic peak current (Ipc) in 0.4 mm print layer thickness when compared to 0.1 and 0.2 mm (Figure 2B, p<0.05, n=4). In addition, there was a significant increase in peak to peak separation (ΔE) in 0.3 mm (p<0.01) and 0.4 mm (p<0.001) when compared to 0.1 mm layer thickness (Figure 2C, n=4).…”
Section: Electrochemical Activity Varies With Orientation and Layer Thickness For Outer And Inner-sphere Redox Moleculesmentioning
confidence: 95%
“…Electrochemical characterisation of these electrodes is shown in Figure 2 for outer sphere redox species hexaamineruthenium (III) chloride. [21] In the vertical orientation print, clear voltammetric peaks were observed (Figure 2A, n=4), with significant reduction in the cathodic peak current (Ipc) in 0.4 mm print layer thickness when compared to 0.1 and 0.2 mm (Figure 2B, p<0.05, n=4). In addition, there was a significant increase in peak to peak separation (ΔE) in 0.3 mm (p<0.01) and 0.4 mm (p<0.001) when compared to 0.1 mm layer thickness (Figure 2C, n=4).…”
Section: Electrochemical Activity Varies With Orientation and Layer Thickness For Outer And Inner-sphere Redox Moleculesmentioning
confidence: 95%
“…The LOD and LDR reported here showed that this technique is technically an improvement over the work of Bonetto et al. [ 213 ]…”
Section: Detection Of Nts Using Cnt‐based Sensorsmentioning
confidence: 57%
“…LOD of 2.4 nM was reported for SE using this electrode in a DPV experiment. The LOD and LDR reported here showed that this technique is technically an improvement over the work of Bonetto et al [213] Table 2 summarizes the efforts made so far in the detection of SE using different CNT-based electrodes from year 2010 to date. This is with a view to visualizing the progress made thus far in the detection of the neurotransmitter.…”
Section: Cnts Enhanced Electrochemical Se Detection (2016-2019)mentioning
confidence: 73%
See 1 more Smart Citation
“…Currently, a huge variety of materials has been employed for building electrochemical sensors aiming to improve their properties such as electrical conductivity, surface area, and mechanical- and chemical stability [ 30 ]. The building material selection pretends to solve some problems of the electrochemical sensors like electrode fouling and overlapping of the redox potential of the molecules presented as analyte [ 31 ].…”
Section: Introductionmentioning
confidence: 99%